The Improvement of the Services Quality through Development of Teachers Personality and Organizational Justice - Kania Rubiati; Sri Setyaningsih; Henny Suharyati (JETL (Journal of Education, Teaching and Learning), 2020)
The quality of teacher services is an important element related to achieving national education goals and developing Indonesian people as a whole. The initial survey of teacher service quality in the Civil Servants in the High School in the city of Bogor has not yet reached maximum results. Therefore, the quality of teacher services is interesting to study. This study aims to find efforts to improve teacher service quality by examining the relationship between teacher service quality with teacher personality variables and organizational justice. The data needed in this study were captured using an instrument in the form of a questionnaire. Before the questionnaire is used as a data collection tool, it must be first analyzed its validity and reliability. This analysis was carried out by testing the instrument to respondents, who had been determined. This trial is intended to determine the feasibility of this instrument as a research instrument. The study also uses correlational statistical methods and analysis of the SITOREM method. The unit of research analysis was a high school civil servant teacher with a population of 279 and a sample of 103 teachers. The results of the study show there is a positive relationship between the teacher's personality and the quality of teacher services with the strength of the relationship ry1 = 0.421 and there is a positive relationship between organizational justice and the quality of the teacher's service with the strength of the ry2 = 0.297 so that the quality of teacher service can be improved through the personality of the teacher and organizational justice. The results of this study indicate that there is a relationship between the teacher's personality and the service quality approach as well as the organizational justice variable with the quality of teacher service both individually and collectively. SITOREM analysis results showed that there should be priority improvements to indicators that are not optimal such as (1) stable emotions (2) open to experience (3) procedural fairness (4) responsiveness (5) attention.